2021
DOI: 10.1038/s41375-021-01461-5
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor MIR139 is silenced by POLR2M to promote AML oncogenesis

Abstract: MIR139 is a tumor suppressor and is commonly silenced in acute myeloid leukemia (AML). However, the tumor-suppressing activities of miR-139 and molecular mechanisms of MIR139-silencing remain largely unknown. Here, we studied the poorly prognostic MLL-AF9 fusion protein-expressing AML. We show that MLL-AF9 expression in hematopoietic precursors caused epigenetic silencing of MIR139, whereas overexpression of MIR139 inhibited in vitro and in vivo AML outgrowth. We identified novel miR-139 targets that mediate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 73 publications
1
22
1
Order By: Relevance
“…Despite a significant correlation between the expression of PDE2A and MIR139 in lung cancer cell lines [40], we and other investigators have shown that miR-139-5p and/or miR-139-3p expression is not correlated to PDE2A expression levels in leukemia [38], gastric [41] and colorectal cancer cells [42]. We have recently shown that MIR139 expression is strongly silenced in MLL-AF9 AML, whereas the expression of Pde2a was not affected [38]. These data indicate that post-transcriptional mechanisms other than splicing and subsequent processing of pri-miR-139 by the microprocessor complex play a role in the stability and processing of miR-139-5p and miR-139-3p.…”
Section: Genomic Localization and Host Gene Pde2acontrasting
confidence: 89%
See 4 more Smart Citations
“…Despite a significant correlation between the expression of PDE2A and MIR139 in lung cancer cell lines [40], we and other investigators have shown that miR-139-5p and/or miR-139-3p expression is not correlated to PDE2A expression levels in leukemia [38], gastric [41] and colorectal cancer cells [42]. We have recently shown that MIR139 expression is strongly silenced in MLL-AF9 AML, whereas the expression of Pde2a was not affected [38]. These data indicate that post-transcriptional mechanisms other than splicing and subsequent processing of pri-miR-139 by the microprocessor complex play a role in the stability and processing of miR-139-5p and miR-139-3p.…”
Section: Genomic Localization and Host Gene Pde2acontrasting
confidence: 89%
“…Clinical data show that acute myeloid leukemia (AML) patients with the lowest miR-139 levels have a poor prognosis [46]. In agreement, we found that Mir139 KO HSPCs gave rise to more and larger colonies when transformed with the MLL-AF9 oncogene in colony-forming unit assays, showing that miR-139-depleted leukemia cells have a growth advantage [38]. Whether MIR139 silencing is a critical early driver of leukemogenesis still needs further investigation.…”
Section: The Effect Of Mir139 Ko On Development and Oncogenesissupporting
confidence: 73%
See 3 more Smart Citations